Molecular nutrition : mother and infant - Vinciguerra, Manlio; Sanchez, Paul Cordero (Academic Press, 2021)
Molecular Nutrition: Mother and Infant presents the impact of diet in early life stages, from pre-conception, throughout pregnancy, and to the infant. The book covers the molecular biology of the cell, genetic machinery and its function, general coverage on diet and nutrition, pregnancy, placenta, weight gain, breast milk, feeding practices, gestational disease, glucose metabolism, immunity, vitamins and minerals. Other topics discusses include fetal programming, bioactive compounds, amino acids, intrauterine growth, one carbon metabolism, overnutrition, genetic risk factors, polymorphisms, folic acid genes, DNA methylation, genes involved in lipid metabolism, microRNAs, epigenetics, transcriptomics and micro RNA. This book will be a welcomed reference for research scientists and practitioners, including nutritionists and dieticians. --